Lifetime difference and CP-violating phase in the B-s(0) system - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (Amer Physical Soc, 2007)
From an analysis of the decay B-s(0)-> J/psi phi, we obtain the width difference between the light and heavy mass eigenstates Delta Gamma equivalent to(Gamma(L)-Gamma(H))=0.17 +/- 0.09(stat)+/- 0.02(syst) ps(-1) and the CP-violating phase phi(s)=-0.79 +/- 0.56(stat)(-0.01)(+0.14)(syst). Under the hypothesis of no CP violation (phi(s)equivalent to 0), we obtain 1/Gamma=tau/(B-s(0))=1.52 +/- 0.08(stat)(-0.03)(+0.01)(syst) ps and Delta Gamma=0.12(-0.10)(+0.08)(stat)+/- 0.02(syst) ps(-1). The data sample corresponds to an integrated luminosity of about 1.1 fb(-1) accumulated with the D0 detector at the Fermilab Tevatron collider. This is the first direct measurement of the CP-violating mixing phase in the B-s(0) system.